Information work today : papers presented at a Symposium for Information Workers held at Liverpool School of Librarianship in September 1966 - Houghton, Bernard (London : Bingley, 1967)
The "Information work today" symposium was designed as a concentrated introduction to information work and lesser known sources of information, and was primarily intended for those scientists, technologists and librarians who had recently moved into information work from either laboratories and workshops or from other non-technical libraries, and who wished to acquire a fuller view of their newly adopted field. The book should also be of value to the practicing information worker as a refresher course.
Includes bibliographical references.
aia 19/06/2017
Loans
Keywords: Technology